2022
DOI: 10.1002/jmri.28198
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric Magnetic Resonance Imaging for Assessing Thymic Epithelial Tumors: Correlation With Pathological Subtypes and Clinical Stages

Abstract: Background World Health Organization classification and Masaoka‐Koga stage are widely used for thymic epithelial tumors (TETs). Reduced field‐of‐view (rFOV) diffusion‐weighed imaging (DWI) proved to improve the image quality. Dynamic contrast‐enhanced (DCE) MRI was commonly used in evaluating tumors. Purpose To investigate the value of multiparametric MRI in evaluating TETs. Study Type Retrospective. Subjects Eighty‐seven participants including 38 low risk (52.08 ± 14.19 years), 30 high risk (52.40 ± 11.35 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…In the same study, the AUC was 0.804 when using an ADC cutoff of 1.25 × 10 -3 mm 2 /sec to differentiate low-risk thymomas from high-risk thymomas and thymic carcinomas. A recent study by Shen et al 18 reported that the mean ADC values of low-risk thymoma, high-risk thymoma, and TC were 1.279 × 10 -3 mm 2 /sec, 0.978 × 10 -3 mm 2 /sec, and 0.661 × 10 -3 mm 2 /sec, respectively. The optimal ADC cutoff to distinguish low-risk thymomas from high-risk thymomas and TCs in the research of Shen et al 18 was 1.193 × 10 -3 mm 2 /sec, which was also lower than the value reported by Razek et al 17 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the same study, the AUC was 0.804 when using an ADC cutoff of 1.25 × 10 -3 mm 2 /sec to differentiate low-risk thymomas from high-risk thymomas and thymic carcinomas. A recent study by Shen et al 18 reported that the mean ADC values of low-risk thymoma, high-risk thymoma, and TC were 1.279 × 10 -3 mm 2 /sec, 0.978 × 10 -3 mm 2 /sec, and 0.661 × 10 -3 mm 2 /sec, respectively. The optimal ADC cutoff to distinguish low-risk thymomas from high-risk thymomas and TCs in the research of Shen et al 18 was 1.193 × 10 -3 mm 2 /sec, which was also lower than the value reported by Razek et al 17 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Shen et al 18 reported that the mean ADC values of low-risk thymoma, high-risk thymoma, and TC were 1.279 × 10 -3 mm 2 /sec, 0.978 × 10 -3 mm 2 /sec, and 0.661 × 10 -3 mm 2 /sec, respectively. The optimal ADC cutoff to distinguish low-risk thymomas from high-risk thymomas and TCs in the research of Shen et al 18 was 1.193 × 10 -3 mm 2 /sec, which was also lower than the value reported by Razek et al 17 . The ADC values of the TETs in our study were lower compared with the results of both Razek et al 17 and Shen et al 18 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue of Journal of Magnetic Resonance Imaging, a publication by Shen et al entitled "Multiparametric MRI for assessing TETs: Correlation with Pathological Subtypes and Clinical Stages" evaluated biomarkers to be integrated into an improved risk prediction model for thymic tumors. 7 The study assessed the value of a combination of DCE-MRIderived parameters and ADC values for differentiation in the WHO classification and Masaoka-Koga staging system. The authors concluded that the quantitative parameters ADC, Ktrans, and Kep were valuable for discrimination of both WHO classification and clinical stage of TETs.…”
mentioning
confidence: 99%